Stable isotopic profile of commercial tank milk in relation to grassland based feed proportions in dairy herd diets - Amy Birkinshaw; Michael Sutter; Rudi Schäufele; Michael Kreuzer; Beat Reidy (Scientific Reports)
Abstract Ours is the first proof-of-concept study to attempt to define stable isotopic ratio (δ) thresholds to ascertain the dietary proportion of grassland-based feeds (GBF) in commercial tank milk. Additionally, the isotopic profile of commercial tank milk produced in Switzerland was characterized. We collected 217 tank milk samples, from 21 dairy farms, over one calendar year to reflect and incorporate seasonal variations in feeding strategies. Thus, a wide range of feeding strategies based on contrasting proportions of total GBF (28–99%) and grazed herbage (0–96%) were represented. Based on mixed-model multiple regression, there was a significant association of δ13C and δ18O values of tank milk and the dietary proportions of GBF and grazed herbage, respectively. For every 10% increase in total GBF, δ13C decreased by 0.673 (R2 = 0.57) and for every 10% increase in grazed herbage, δ18O increased by 0.125 (R2 = 0.51). With this information, δ13C and δ18O values of bulk milk may be suitable starting points for the development of reliable indicators to assess and control the proportion of total GBF and grazed herbage in dairy farm diets. Commercial tank milk produced in Switzerland has a mean value of − 26.0, 5.69, − 7.03 and − 53.4 for δ13C, δ15N, δ18O and δ2H, respectively.